GLORIA and Study of Cataclysmic Variables - R. Hudec; V. Šimon (Acta Polytechnica CTU Proceedings, 2015)
We report here on the ongoing EU FP7 Project GLORIA (GLObal Robotic-telescopes Intelligent Array) with emphasis on possibility of investigation of cataclysmic variables by users. GLORIA will enable the first free and open-access network of robotic telescopes in the world. We show several examples of the not often used topics (but suitable for GLORIA) for the studies of activity of cataclysmic variables, e.g. search for outbursts in intermediate polars and the fluctuations of brightness in their quiescence, and investigation of the optical counterparts of supersoft X-ray sources.